The Effects of Japanese Foreign Exchange Market Interventions on the Yen/U.S. Dollar Exchange Rate Volatility - Michael Frenkel; Christian Pierdzioch; Georg Stadtmann (Kiel Institute for World Economics (IfW), 2003)
Previous studies have mainly used reports in the financial press to analyze the link between the interventions of the Bank of Japan (BoJ) and exchange rate volatility. We use official intervention data for the period 1993-2000 that were released only recently by the BoJ and find that the interventions of the BoJ increased the volatility of the yen/U.S. dollar exchange rate. We find that that the interventions of the BoJ, in particular those interventions not reported in the financial press, were positively correlated with exchange rate volatility.
Keywords: E58; G15; F33; F31; 330; Foreign exchange market interventions; Exchange rate volatility; Bank of Japan; Wechselkurspolitik; Japanisch; Wirtschaftspolitische Wirkungsanalyse; Wechselkurs; Volatilität; Japan; Vereinigte Staaten